Comparative genomic analysis of antibiotic resistance and virulence genes in Staphylococcus aureus isolates from patients and retail meat - Alkuraythi, Dalal M.; Alkhulaifi, Manal M.; Binjomah, Abdulwahab Z.; Alarwi, Mohammed; Mujallad, Mohammed I.; Alharbi, Saleh Ali; Alshomrani, Mohammad; Gojobori, Takashi; Alajel, Sulaiman M. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Staphylococcus aureus is a significant human pathogen that poses a threat to public health due to its association with foodborne contamination and a variety of infections. The factors contributing to the pathogenicity of S. aureus include virulence, drug resistance, and toxin production, making it essential to monitor their prevalence and genetic profiles. This study investigated and compared the genomic characteristics of S. aureus isolates from retail meat and patients in Saudi Arabia. Methods: A total of 136 S. aureus isolates were obtained between October 2021 and June 2022:84 from patients and 53 from meat samples in Riyadh, Saudi Arabia. S. aureus isolates were identified using conventional methods and MALDI-TOF MS, and methicillin-resistant S. aureus (MRSA) was identified using VITEK2 and BD Phoenix systems. MRSA was confirmed phenotypically using chromogenic agar, and genotypically by detecting mecA. Genomic data were analyzed using BactopiaV2 pipeline, local BLAST, and MLST databases. Results: Antibiotic resistance genes were prevalent in both meat and patient S. aureus isolates, with high prevalence of tet38, blaZ, and fosB. Notably, all S. aureus isolates from patients carried multidrug-resistant (MDR) genes, and a high percentage of S. aureus isolates from meat also harbored MDR genes. Phenotypically, 43% of the S. aureus isolates from meat and 100% of the patients’ isolates were MDR. Enterotoxin genes, including selX, sem, and sei, exhibited high compatibility between meat and patient S. aureus isolates. Virulence genes such as cap, hly/hla, sbi, and isd were found in all S. aureus isolates from both sources. Conclusion: Our study established a genetic connection between S. aureus isolates from meat and patients, showing shared antibiotic resistance and virulence genes. The presence of these genes in meat derived isolates underscores its role as a reservoir. Genomic relatedness also suggests potential transmission of resistance between different settings. These findings emphasize the necessity for a comprehensive approach to monitor and control S. aureus infections in both animals and humans.